The Role of Xanthine Oxidase in Pregnancy Complications: A Systematic Review - Lorenzo Annesi; Giovanni Tossetta; Claudio Borghi; Federica Piani (MDPI AG, 2024)
Xanthine oxidoreductase (XOR) is an enzyme involved in the oxidation of hypoxanthine and xanthine to uric acid. XOR has two isoforms: xanthine dehydrogenase and xanthine oxidase (XO). XO plays a major role in oxidative stress, causing the formation of reactive oxygen species. In the present study, we aimed to summarize the evidence on the association between XO and pregnancy complications. The PRISMA checklist guided the reporting of the data. We conducted systematic searches in the PubMed and Web of Science databases to identify all human studies investigating XO in pregnancy diseases up to June 2024. A total of 195 references have been identified and 14 studies were included. Most studies focused on women with PE and GD. Overall, all the included studies found a statistically significant increase in maternal, placental, and/or fetal XO levels, activity, or tissue expression in women with pregnancy complications, compared to those with uncomplicated pregnancies. Although promising, the quality and dimension of the included studies do not allow for a definitive answer to the question of whether XO may play a crucial role in pregnancy complications. Future studies are warranted to confirm if XO could represent a prognostic and therapeutic marker in pregnancy complications and their impact on long-term maternal and offspring cardiovascular health.